2015
DOI: 10.7453/gahmj.2015.061
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as a Therapy for Adolescents and Young Adults with Cystic Fibrosis: A Pilot Study

Abstract: Rationale:Yoga has been shown to improve outcomes in patients with asthma but has not been investigated in cystic fibrosis (CF) patients.Methods:This was a prospective pilot study to evaluate the safety of a standardized yoga program among CF patients aged 12 to 25 years. Participants engaged in a 50-minute yoga session twice weekly for 8 weeks conducted by a certified yoga instructor using a standardized program designed to be safe for health-compromised individuals. Yoga sessions were individual to avoid tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…Twenty participants completed the yoga program offered at our site. As with Ruddy et al [76], the subjects in our study tolerated the yoga therapy safely.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Twenty participants completed the yoga program offered at our site. As with Ruddy et al [76], the subjects in our study tolerated the yoga therapy safely.…”
Section: Discussionsupporting
confidence: 86%
“…After systematic review [75, 76] we found only one prior study performed by Ruddy et al to evaluate yoga as a complementary therapeutic practice in children with cystic fibrosis [76]. The study presented here is the largest to date and the first with a primary aim is to evaluate therapeutic benefit; however, this is a pilot study and the results should be considered suggestive but not conclusive.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, there was no significant change in the other domain scores: the self-reported respiratory symptom score, FEV 1 , weight, or Ease of Breathing Score. No studies have been done in NCFB ( 41 ).…”
Section: Possible Treatment Determinants Of Qolmentioning
confidence: 99%